Diagnostic value of miR-92a in asymptomatic carotid artery stenosis patients and its ability to predict cerebrovascular events - Gang Chen; Jianwei Gao; Yuguo Sheng; Xinqiang Han; Xingang Ji; Mengpeng Zhao; Jian Wu (BMC, 2020)
Abstract Background Early diagnosis of asymptomatic carotid artery stenosis (ACAS) is important to prevent the incidence of cerebrovascular events. This study aimed to investigate the circulating expression of microRNA-92a (miR-92a) in ACAS patients and evaluate its diagnostic value for ACAS and predictive value for cerebrovascular events. Methods Circulating expression of miR-92a was measured using quantitative real-time PCR. Chi-square test was used to analyze the association of miR-92a with ACAS patients' clinical characteristics. A receiver operating characteristic (ROC) was used to evaluate the diagnostic value of miR-92a, and the Kaplan-Meier method and Cox regression analysis were used to assess the predictive value of miR-92a for cerebrovascular events. Results Serum expression of miR-92a was higher in ACAS patients than that in the healthy controls (P <  0.001), and associated with patients' degree of carotid stenosis (P = 0.013). The elevated miR-92a expression could distinguish ACAS patients from healthy individual, and was an independent predictive factor for the occurrence of cerebrovascular events (P = 0.015). Conclusion The data from this study indicated that circulating increased miR-92a may serve as a noninvasive diagnostic biomarker for ACAS and a potential risk factor for the future onset of cerebrovascular events.